PERCEPATAN JURNAL KEWIRAUSAHAAN DAN BISNIS MENUJU AKREDITASI NASIONAL - Susantiningrum Susantiningrum; Eddy Triharyanto; Bara Yudhistira; Dimar Hantari (Universitas Sebelas Maret, 2019)
Jurnal Kewirausahaan dan Bisnis (JKB) has p-ISSN and e-ISSN. In 2017 JKB socialization activities were carried out to publish the journal to all regions in Indonesia and to attract more varied writers, especially those from outside Universitas Sebelas Maret (UNS). Furthermore, JKB development activities are needed towards reputable journals by adopting the Direktorat Jenderal Pendidikan Tinggi Regulation No. 1 of 2014 concerning Accreditation Guidelines for Scientific Issues. This study aims to improve the quality and capacity of management study centers, especially in managing Jurnal Kewirausahaan dan Bisnis towards reputable journals, such as by preparing national journal accreditation requirements. Activities that have been carried out included: initial coordination of activities, submitting to the national index institute, workshop on simulation of journal appraisal towards national accreditation, and workshop on the national accreditation program for JKB.Keywords: journal, institution, entrepreneurship, accreditation